In Würde lernen: Wege des Kompetenzerwerbs - selbstbestimmt, einprägsam und angstfrei - Reimann-Pöhlsen, Inga, (transcript, 2020)
The subjective perception of learning worlds and the potential of particularly effective moments. For fearless and dignified learning.